The common indoor air pollutant α-pinene is metabolised to a genotoxic metabolite α-pinene oxide. (4th March 2022) - Waidyanatha, Suramya; Black, Sherry R.; Witt, Kristine L.; Fennell, Timothy R.; Swartz, Carol; Recio, Leslie; Watson, Scott L.; Patel, Purvi; Fernando, Reshan A.; Rider, Cynthia V.
Abstract: α-Pinene caused a concentration-responsive increase in bladder hyperplasia and decrease in sperm counts in rodents following inhalation exposure. Additionally, it formed a prospective reactive metabolite, α-pinene oxide. To provide human relevant context for data generated in animal models and explore potential mechanism, we undertook studies to investigate the metabolism of α-pinene to α-pinene oxide and mutagenicity of α-pinene and α-pinene oxide. α-Pinene oxide was formed in rat and human microsomes and hepatocytes with some species differences. Based on area under the concentration versus time curves, the formation of α-pinene oxide was up to 4-fold higher in rats than in humans. While rat microsomes cleared α-pinene oxide faster than human microsomes, the clearance of α-pinene oxide in hepatocytes was similar between species. α-Pinene was not mutagenic with or without induced rat liver S9 in Salmonella typhimurium or Escherichia coli when tested up to 10 000 µg/plate while α-pinene oxide was mutagenic at ≥25 µg/plate. α-Pinene was metabolised to α-pinene oxide under the conditions of the bacterial mutation assay although the concentration was approximately 3-fold lower than the lowest α-pinene oxide concentration that was positive in the assay, potentially explaining the lack of mutagenicity observed with α-pinene.